2023
DOI: 10.3390/plants12142724
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Aspergillus tubingensis GX3′ Fermentation against Meloidogyne enterolobii in Tomato (Solanum lycopersicum L.)

Abstract: Meloidogyne enterolobii is one of the most virulent root-knot nematodes (RKNs). Aspergillus tubingensis Raoul Mosseray, 1934, is used to produce bioactive substances, enzymes, and secondary metabolites. However, no research has been conducted yet on the efficacy of A. tubingensis against plant-parasitic nematodes. Thus, the novel research was planned to evaluate the biocontrol efficacy of A. tubingensis fermentation against M. enterolobii. The findings showed that egg hatching inhibition and mortality of M. en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
(90 reference statements)
1
4
0
Order By: Relevance
“…Results from this study indicated that the application of A. tubingensis WF01 significantly not only decreased the infection of M. incognita but also promoted plant growth ( Figure 5 ). Our findings corroborated the results of Kriaa et al (2015) , Zhao et al (2018) , and Sikandar et al (2023) , who demonstrated that A. tubingensis effectively protected plants against phytopathogens and meanwhile increased plant length and fresh mass.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Results from this study indicated that the application of A. tubingensis WF01 significantly not only decreased the infection of M. incognita but also promoted plant growth ( Figure 5 ). Our findings corroborated the results of Kriaa et al (2015) , Zhao et al (2018) , and Sikandar et al (2023) , who demonstrated that A. tubingensis effectively protected plants against phytopathogens and meanwhile increased plant length and fresh mass.…”
Section: Discussionsupporting
confidence: 91%
“…Strain WF01 demonstrated remarkable nematicidal efficacy against M. incognita J2s. The WF01 culture broth resulted in 100% juvenile mortality to M. incognita only needed 24 h of exposure time ( Figure 2 ), which was shorter than that of the A. tubingensis GX3 to M. enterolobii (72 h) ( Sikandar et al, 2023 ). This is possibly due to the differences in strains and target nematodes.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Novel biorational strategies have been evaluated for the M. enterolobii control. For example, P. lilacinum and Pochonia chlamydosporia conidia reduced by 80% the hatching of this nematode under in vitro conditions [14]; Aspergillus tubingensis fermentation inhibited M. enterolobii hatching and caused 100% mortality of its J2 in in vitro conditions and significantly reduced the infestation of greenhouse tomato plants [42]; and indole 3-butyric acid prevented M. enterolobii infestation in guava plants [43]. Although the applications of M. carneum reduce the population of M. enterolobii in heavily infested soils, it may be interesting to use this biological control with other novel control strategies such as those described above and also including crop rotation and the use of resistant cultivars to reduce the nematode population in less time [20].…”
Section: Discussionmentioning
confidence: 96%